Prophylactic Central Neck Dissection to Improve Disease-Free Survival in Pediatric Papillary Thyroid Cancer - Ngo, Duy Quoc; Le, Duong The; Le, Quang (Frontiers in Oncology, 2022)
Background: Pediatric PTC is a rare disease. Although, the prognosis is excellent and the mortality rate is low, the role of prophylactic central neck dissection is still the subject of debate. The aim was to evaluate both the role and safety of prophylactic central neck dissection (CND) in managing pediatric papillary thyroid cancer (PTC), especially in respect of disease-free survival (DFS). Patients and methods: In this retrospective study, we collected 54 pediatric cN0 PTC patients (≤ 18 years of age) who were treated from January 2014 to January 2021 at a high-volume thyroid surgery center. Patients were divided into two groups based on the status of prophylactic CND. We analyzed the factors related to the clinicopathological features and recurrence of PTC in children. Results: Of the 54 cN0 patients, 35 underwent prophylactic CND and 19 patients did not undergo prophylactic CND. The two groups were similar in clinical and pathologic features, such as age, gender, tumor size, multifocal status, and follow-up time. The average DFS was 84.4 ± 2.7 months. Log-rank tests on Kaplan-Meier curves revealed that age, gender, tumor size, multifocality, and extrathyroid extension did not relate to DFS time. Furthermore, DFS time was not affected by the extent of thyroidectomy (p=0.07) or RAI treatment (p=0.21). Prophylactic CND was found to increase DFS time for pediatric patients with cN0 PTC (p = 0.003). There was no statistically significant difference in complications such as transient hypocalcemia (p=0.15) and transient recurrent laryngeal nerve injury (p=0.37) between the prophylactic CND group and the no-prophylactic CND group. Conclusion: Prophylactic CND was found to be associated with increased DFS and not with increased rates of complications after surgery.